Lateral-torsional buckling of high strength steel beams: experimental resistance - Tankova, Trayana (2021)
EN 1993-1-1 gives stability design rules for columns, beams and beam & ndash;columns up to S460, whereas EN 19931-12 gives additional guidance for S500 up to S700. Recent studies show that high strength steel members may be designed using improved buckling curves, where the enhanced behaviour is usually attributed to the improved material properties but mainly due to the more favourable residual stress distribution. The behaviour of unrestrained beams in HSS has not been widely studied. At present in EN 1993-1-1, the design rules for lateral-torsional buckling of beams are not dependent on the steel grade, meaning that the code does not distinguish between beams in conventional strength steel or HSS. In pursuit of an answer to the mentioned shortcomings, the present research is based on the experimental programme covering 12 full-scale tests, residual stress measurements, advanced numerical models and analytical derivations. The experiments cover different steel grades up to S690, welded and hot-rolled sections, homogeneous and hybrid (flanges in HSS and web in mild steel), double and mono-symmetric sections as well as variations in the cross-section class. This paper provides an overview of the experimental programme, discusses the results for lateral-torsional buckling of beams, and presents an advanced numerical model that was calibrated to the experimental results including the measured residual stress distribution and geometrical properties of the members. The numerical model was explored to assess various assumptions for the member imperfections, and these are further compared with code recommendations.